Effects of Duloxetine in Rats Trained to Discriminate Between 2- and 22- hr Food Deprivation - Gomer, Bailey; Berti, Brianna; Vossen, Taylor J.; Reed, Krystal A.; Nemec, Dillon J.; Schultz, Andrew T.; Johnson, Amy R.; Toddes, Carlee; Vanden Avond, Mark A.; Drengler, Mackenzie M.; Hendrickson, Elizabeth J. (My University, 2013)
Duloxetine inhibits serotonin and norepinephrine transporters, and is clinically used to treat depression, pain, and generalized anxiety disorder. Duloxetine has been shown to reduce food intake in several species. The purpose of this study was to examine the effects of duloxetine in non-restricted rats trained to discriminate between 22- and 2-hour food deprivation to gain better understanding of neurochemicals mediating the discriminative stimulus effects of 22-hour food deprivation.
Color poster with text and graphs.
Keywords: Duloxetine--Side effects; Posters; Discrimination learning; Rats--Training; Hunger--Psychological aspects